Amperometric Biosensors for Real Time Assays of Organophosphates - Kamil Kuca; Daniel Jun; Miroslav Pohanka (Sensors, 2008)
An amperometric biosensor based on acetylcholinesterase (AChE) immobilized in gelatin was used to develop an assay for the organophosphate paraoxon. The more traditional manner employing preincubation was used for comparison between measurement procedures, although the aim of the study was to examine the performance of the biosensor for real time monitoring of organophosphates. The biosensor was immersed in a reaction chamber and paraoxon was injected inside. We were able to detect 200 pg of paraoxon within one minute or 2.5 ppb when the biosensor was preincubed in the sample solution for 15 minutes. The practical impact and expectations are discussed.